2024
DOI: 10.1037/mac0000167
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious memory promotes successful adaptation and enriches the self.

David B. Pillemer,
Dorthe K. Thomsen,
Robyn Fivush

Abstract: Autobiographical memory theory and research have focused primarily on memories of personally experienced events. We propose that remembering specific memories and life stories recounted by others, termed vicarious memory (VM), is an essential component of personal identity and successful living. We examine (a) the broad adaptive significance of VM; (b) the importance of VM at different developmental periods, with a focus on early childhood; (c) the role played by VM when people confront new and challenging cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 121 publications
0
0
0
Order By: Relevance
“…Vicarious memories are a unique form of memory that allows individuals to make the experiences of other people who are close to them as their own. The target article (Pillemer et al, 2024) provided an engaging view of vicarious memories and the ways that they may manifest in individuals' lives. Their work furthers the field immensely, moving us closer to a formal theory of vicarious remembering.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Vicarious memories are a unique form of memory that allows individuals to make the experiences of other people who are close to them as their own. The target article (Pillemer et al, 2024) provided an engaging view of vicarious memories and the ways that they may manifest in individuals' lives. Their work furthers the field immensely, moving us closer to a formal theory of vicarious remembering.…”
Section: Discussionmentioning
confidence: 99%
“…As such, when considering narrative ecology (Lind, 2023), we postulate vicarious memories would typically be derived from the microlevel. Pillemer et al (2024) provided a much more open view of the source of vicarious memories, including family, friends, support group members, work colleagues, and others. They also suggested that the listener does not need to hear the memory firsthand but can hear it through others (i.e., gossip; Dunbar, 2004) and that learning of the vicarious memory may not always occur in person.…”
Section: Source Of Vicarious Memoriesmentioning
confidence: 99%
See 3 more Smart Citations